The Deputy Vice Chancellor (A&A) Roadshow - Saharudin, Ramli; Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
30 July 2012. As part of a roadshow session, the Deputy Vice Chancellor (DVC) (A&A), Professor Dr Badrulhisham Abdul Aziz, hold an interactive discussion with CMLHS academic staff on 30 July in order to obtain feedback on academic issues.